A GIS Based Approach for Finding Association between Air Pollution, Factories and Population Density in North Macedonia - Stefanovska, E.; Kralevska, A.; Abazi, A.; Naumoski, Andreja (IEEE, 2021)
Air pollution is a serious problem in North Macedonia. In this project all the air quality stations in North Macedonia were mapped along with the closest factories to these stations. Later, the collected data was used to analyze how the number of factories and the population density around air quality stations correlates with the amount of pollution measured by given station. Comparison between air quality data collected during whole year and only in winter months was also made. This whole process was carried in ArcGIS, a software which has variety of spatial visualization and processing tools. Our work shows that, as expected, there is a positive correlation between the number of factories close to a given station and the pollution that it measures. The same pattern is true for the population density, too. We hope that this research paper will have a positive impact for solving the air pollution problem and perhaps changes towards improving the whole situation will be made, especially in the areas identified with the highest amount of pollution.
Keywords: air pollution; factories; population density; GIS